Prospects of Introduction of Integrated Quality Management Systems at Enterprises of Uzbekistan - Azimov, Rustam Sadykovich (Transactions on Engineering and Computing Sciences, 2025)
This article explores the prospects of implementing integrated quality management systems in enterprises across Uzbekistan, focusing on the insurance sector. The ISO 9001:2015 standard is highlighted as a universally applicable framework that aligns well with the principles of financial organization. Through thorough implementation of specific sections of the standard, insurance companies can enhance customer service quality and strategically position themselves in domestic and foreign markets. The government's role in encouraging certification and providing benefits for compliant enterprises is discussed, alongside global statistics on ISO certification. Case studies, such as the implementation at "Uzbekinvest" Insurance Company, demonstrate the positive impact of quality management systems on business performance.